Training on The Use of Cloud Computing Based Online Data Storage Application at SMAN 1 Citeureup - Alviana, Sopian; Kurniawan, Bobi (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
This service programme aims to provide training to teachers at SMAN 1 Citeureup in using online academic data storage media. SMAN 1 Citeureup is one of the schools based on digitalization in academic and non academic activities. The stages carried out in this service include planning, preparation, training, and evaluation. In the development of cloud computing based data storage applications needed for academic data storage. The results show that after attending training with the service scheme the teachers can understand the features in the data storage media. It can bee seen from the response value that there is an increase from 3.48 which has a high level of understanding to a very high scale after training with a value of 4.31.